2021
DOI: 10.1007/s10142-021-00803-x
|View full text |Cite
|
Sign up to set email alerts
|

Pepsinogen C expression–related lncRNA/circRNA/mRNA profile and its co-mediated ceRNA network in gastric cancer

Abstract: BackgroundThe expression of pepsinogen C (PGC) is considered an ideal negative biomarker of gastric cancer, but its pathological mechanisms remain unclear. This study aims to analyze competing endogenous RNA (ceRNA) networks related to PGC expression at a posttranscriptional level and build an experimental basis for studying the role of PGC in the progression of gastric cancer. Materials and methodsRNA sequencing technology was used to detect the differential expression pro les of PGC-related long non-coding (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The application of spatial transcriptomics, bulk RNA sequencing, and bulk proteomics as well as other novel omics technologies for clinical sample analysis is currently affected by sample location, with different tumor heterogeneity and purity (Cao et al 2021 ; Cui Zhou et al 2022 ; Hwang et al 2022 ). To construct the purity-independent regulatory model in pancreatic cancer, we adopted the ceRNA mechanism, which forms a link between the functions of protein-coding mRNAs and noncoding RNAs (such as lncRNAs, circRNAs, and miRNAs, including NamiRNAs) (Bailey et al 2016 ; Liang et al 2019 ; Yan et al 2021 ) and has been considered a post-transcriptional regulation mechanism that is widely involved in the pathological processes of various cancers, including breast, colon, lung, gastric, and pancreatic cancers (Abdollahzadeh et al 2019 ; X Liu et al 2023b ; Qi et al 2015 ; Shuwen et al 2018 ; Yan et al 2021 ). By preserving the correlation between RNA interaction pairs under different tumor purities, we constructed the three-gene purity-independent network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of spatial transcriptomics, bulk RNA sequencing, and bulk proteomics as well as other novel omics technologies for clinical sample analysis is currently affected by sample location, with different tumor heterogeneity and purity (Cao et al 2021 ; Cui Zhou et al 2022 ; Hwang et al 2022 ). To construct the purity-independent regulatory model in pancreatic cancer, we adopted the ceRNA mechanism, which forms a link between the functions of protein-coding mRNAs and noncoding RNAs (such as lncRNAs, circRNAs, and miRNAs, including NamiRNAs) (Bailey et al 2016 ; Liang et al 2019 ; Yan et al 2021 ) and has been considered a post-transcriptional regulation mechanism that is widely involved in the pathological processes of various cancers, including breast, colon, lung, gastric, and pancreatic cancers (Abdollahzadeh et al 2019 ; X Liu et al 2023b ; Qi et al 2015 ; Shuwen et al 2018 ; Yan et al 2021 ). By preserving the correlation between RNA interaction pairs under different tumor purities, we constructed the three-gene purity-independent network.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between genome alteration of integrins and treatment resistance remains unclear. In this article, we conducted a pan-cancer multi-omics analysis of integrin superfamily genes and identified the most critical integrin in pancreatic cancer by constructing a purity-independent RNA regulation network (Yan et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other pro‐fibrotic factors, such as FN1, COLIA1 and TGF‐β1, and pro‐inflammatory factors, such as IL‐6 and IL‐1β, were all suppressed by CuE‐induced increase in let‐7c‐5p as well. Based on the previous study reported by Yan et al, let‐7c‐5p has a regulatory effect on PGC/PPARγ axis 25 . The PPARγ is a central factor contributing to the alternative expression of FN1 and COLIA1 14 as well as to NF‐κB‐mediated pro‐inflammatory pathways such as IL‐6 and IL‐1β 26 .…”
Section: Discussionmentioning
confidence: 96%
“…Antagomir group, mice administered with 100 mg/ml nicotine and 0.5 mg/kg/day of CuE for 4 weeks along with tail injection of let-7c-5p antagomir twice a week for 4 weeks Based on the previous study reported by Yan et al, let-7c-5p has a regulatory effect on PGC/PPARγ axis. 25 The PPARγ is a central factor contributing to the alternative expression of FN1 and COLIA1 14 as well as to NF-κBmediated pro-inflammatory pathways such as IL-6 and IL-1β. 26 Thus, except for modulating the level of NGF via let-7c-5p, there might be a potential regulatory sequence from CuE to pro-fibrotic factors, such as FN1, COLIA1 and TGF-β1, and pro-inflammatory factors, such as IL-6 and IL-1β, via the modulation of let-7c-5p.…”
Section: Discussionmentioning
confidence: 99%
“…11 genes (BIRC5, CCNB1, CDC20, NUF2, CEP55, NDC80, MKI67, PTTG1, RRM2, TYMS, and UBE2C) related to breast cancer proliferation that had been validated by experiment were obtained from the published articles [ 29 ]. After this, correlation analysis of DHCR7 expression and tumor stage, survival analysis, proliferation related genes was performed using “ggcorrplot” R packages [ 30 , 31 ]. The Kaplan-Meier plotter was used for gene survival analysis ( http://kmplot.com/analysis , accessed in January 2023).…”
Section: Methodsmentioning
confidence: 99%